Multiple Sclerosis: The Role of MR Imaging - Ge, Y. (American Journal of Neuroradiology, 2006)
Summary: MR offers by far the most sensitive technique for detecting multiple sclerosis (MS) lesions and has proved to be an important paraclinical tool for diagnosing MS and monitoring therapeutic trials. Technologic advances of MR in recent years have dramatically improved our understanding of MS disease. This review will focus on the contribution of MR imaging in MS and provide a discussion of conventional and advanced nonconventional MR techniques with regard to current findings, clinical correlations, and future directions.